Ventricular arrhythmias in patients with functional mitral regurgitation and implantable cardiac devices: implications of mitral valve repair with Mitraclip. (25th November 2020) - Benito Gonzalez, T; Freixa, X; Godino, C; Taramasso, M; Estevez-Loureiro, R; Pascual, I; Serrador, A; Nombela, L; Grande, D; Cruz, I; San Antonio, R; Galasso, M; et al.
Abstract: Background: Limited information has been reported regarding the impact of percutaneous mitral valve repair (PMVR) on ventricular arrhythmic (VA) burden. The aim of this study was to address the incidence of VA and appropriate antitachycardia implantable cardiac defibrillator (ICD) therapies before and after PMVR. Methods: We retrospectively analyzed all consecutive patients with heart failure with reduce left ventricular ejection fraction, functional mitral regurgitation grade 3+ or 4+ and an active ICD or cardiac resynchronizer who underwent PMVR in any of the eleven recruiting centers. Only patients with complete available device VA monitoring from one-year before to one year after PMVR were included. Baseline clinical and echocardiographic characteristics were collected before PMVR and at 12-months follow-up. Results: 93 patients (68.2±10.9 years old, male 88.2%) were enrolled. PMVR was successfully performed in all patients and device success at discharge was 91.4%. At 12-months follow-up, we observed a significant reduction in mitral regurgitation severity, NT-proBNP and prevalence of severe pulmonary hypertension and severe kidney disease. Patients also referred a significant improvement in NYHA functional class and showed a non-significant trend to reserve left ventricular remodeling. After PMVR a significant decrease in the incidence of non-sustained ventricular tachycardia (VT) (5.0–17.8 vs 2.7–13.5, p=0.002), sustained VT or ventricular fibrillation (0.9–2.5 vs 0.5–2.9, p=0.012) and ICD antitachycardia therapies (2.5–12.0 vs 0.9–5.0, p=0.033) were observed. Conclusion: PMVR was related to a reduction in arrhythmic burden and ICD therapies in our cohort. Funding Acknowledgement: Type of funding source: None